PENGARUH VARIASI MEDIA PENDINGIN TERHADAP NILAI KEKERASAN PADUAN GEAR SPROCKET AISI 1020 DENGAN TIMAH MELALUI HEAT TREATMENT - Anhar, Muh Aan (JURNAL SIMETRIK, 2020)
Study the effect of cooling media variations on the hardness value of AISI 1020 gear sprocket alloys and tin with heat treatment. This research is to find out the combination of AISI 1020 gear sprocket with tin, with a heat treatment process carried out with temperatures reaching 700ÂºC and held for 15 minutes, with air conditioning media, SAE 40 oil and water, and carried out heat treatment with hardness testing on each material with differences in the cooling media using the Rockwell method. From the results of the test, different cooling media, different cooling rates are obtained and produce different hardness changes. In testing the data obtained in accordance with the results of heat treatment which is continued by cooling the air gives the lowest hardness value (51.2 HR), while cooling with oil and water is higher, respectively 54 HR and 58.4 HR.